Solution-focused Brief Counseling Guidebook: Theoretical Validity and Effectiveness in Reducing Student’s Social Anxiety - Purwani, Wayan; Suranata, Kadek; Gading, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2021)
Social anxiety is one of the psychological problems faced by most of students. Several research findings have revealed negative effects that arise due to the high level of social anxiety experienced by students. Based on this phenomenon, schools play a major role in efforts to minimize the level of social anxiety experienced by students through optimizing guidance and counseling services. This research and development aim at testing the acceptability and effectiveness a solution-focused brief counseling guidebook to minimize students' social anxiety. The development procedure using 4D steps, such as, define, design, develop, and desimination of the product. The amount five judgment involve to validating the contents of guidebook. For the piloting, one group pretest-post test experimental procedure involve 15 junior high school students. The data analysis for judgments results show that the counseling guidebook developed in this study has a special content validity index (CVI). Based on the results of the piloting study, counseling guidebookÂ a solution-focused brief counseling guidebook with the miracle question technique was effective in reducing students' social anxiety. The results of this study contribute to the optimization of guidance and counseling services in schools.